SANKSI YANG DAPAT DI KENAKAN TERHADAP KORPORASI YANG TERLIBAT PIDANA - Sopian, Muhamad; Multiwijaya, Vience Ratna; Suar, Aprima (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: As corporations grow increasingly rapidly in the field of economic activity, what is called corporate crime emerges. Corporate crime is an Extra Ordinary Crime. In fact, the impact is not just a momentary loss, but has an impact for a very long time. Therefore, Muladi believes that the idea of punishing corporations through criminal policies is becoming increasingly stronger and important. The recognition of corporations as subjects of criminal law means that corporations can be held accountable. This also means that in both academic and practitioner circles, special crimes called corporate crimes are considered crimes whose perpetrators (corporations) can be held accountable under criminal law. Discussing the problems in this scientific work assignment, the author tries to conduct a scientific analysis using the theory of punishment, namely that a person will not be punished if there is no mistake. Corporate criminal liability cannot be separated from the two subjects of criminal law in corporate crimes, namely the person as manager and the corporation itself. So that in relation to the position of the corporation and the nature of corporate criminal liability in corporate crimes, there are three models of corporate criminal liability, namely the management as the creator and the manager who is responsible, the corporation as the maker and the management are responsible, the corporation as the maker and also the responsible. Prevention of corporate crime can be done in the following ways. The government and legal authorities must provide strict supervision to legal entities and take firm action if corporate crime occurs. Strict supervision/control will narrow the space for a legal entity to commit violations. The role and participation of the community in monitoring violations and crimes committed by corporations and cooperation from various parties, namely the government, law enforcement officials and the community to prevent corporate crimes in monitoring every activity of a corporation.Keywords: Sanctions, Imposed on Corporations, Involved in Crime.